Eco-friendly approaches for dyeing multiple type of fabrics with cationic reactive dyes. (1st November 2017) - Xiao, Hang; Zhao, Tao; Li, Chun-Hong; Li, Meng-Ying
Abstract: The water pollution and water consumption have become two big challenges to the sustainable development in the textile dyeing industry. In this work, a series of multifunctional cationic reactive dyes were synthesized to reduce the consumption of auxiliary chemicals and fresh water in dyeing process. The obtained cationic reactive dyes based on azobenzene were characterized by fourier transform infrared spectra, nuclear magnetic resonance hydrogen spectroscopy and liquid chromatography mass spectrometry. The dyeing properties of cotton fabrics in the case of low-salt dyeing at various temperature and salt concentration were discussed in terms of dye exhaustion and fastness properties. The results show that, despite a small quantity of electrolyte being present in the dye bath, a high percentage of dye exhaustion and good fastness properties can be obtained. Three cationic reactive dyes were used to coloration of acrylic, wool, silk, and nylon6 fabrics at different dye concentration. The results show that the similar K/S value on these fabrics can be achieved. The cationic reactive dyes as the multifunctional dyes instead of traditional dyes could be applied in one-bath one-step dyeing for acrylic/wool blend fabrics. The dyed blend fabrics can obtain good levelling properties and fastness properties. The application of cationic reactive dyes in low-salt dyeing of cotton fabrics is a cleaner method that can reduce the consumption of auxiliary chemicals. Compared to conventional process, the one-bath one-step dyeing of blend fabrics with cationic reactive dyes does not require a large amount of water and energy, indicating that cationic reactive dyes have potential application in the cleaner production of textile industry. Highlights: Three novel cationic reactive dyes based on azobenzene have been synthesized. Cationic reactive dyes are adopted for low-salt dyeing of cotton fabrics. Cationic reactive dyes can be applied in one-bath one-step dyeing of blend fabrics. Utilization of cationic reactive dyes has high economical and environment efficiency.